A brief historical overview of bioethical activism in Croatia : as an impetus for the development of an educational model of bioethical activism - Kelam, Ivica (Array, 2020)
There has been a universal agreement in the last couple of decades that bioethics education at all levels should be provided to citizens through the adoption of the Universal Declaration on the Human Genome and Human Rights by the UNESCO General Conference in 1997 and by the United Nations General Assembly in 1998. The work of bioethical educators in moral and (bio)ethical values was applied to the issues raised by modern science and technology. The process of learning is also recognized as being the result of complex interacting influences. Teaching in a bioethical context must recognize these interconnections because of the internal application to and impact on peoples’ lives. Furthermore, teaching in a bioethical context needs to use pedagogies that engage students in participatory activities to enable the development of multiple dimensions of knowledge. These dimensions include the scientific content as well as the personal, social, and emotional aspects associated with any particular bioethical issue. Therefore, it is crucial to highlight the importance of focusing on the nature of the controversy, recognizing that opinions are based on particular worldviews and critical reflection of personal views, as well as promoting open-mindedness or willingness to accommodate new views and develop a new bioethical perspective on life. The paper presents several examples of bioethical activism in Croatia that provided an impetus for teaching students in bioethical activism at the Faculty of Education. I will mention an example of the inclusion of the NGO Pobjede in a bioethical course on the subject of the ethical relation to animals. An example of NGO Pobjede activity was a stimulating example of bioethical activism for students.